SOME FEATURES OF CERTAIN PHRASEOLOGICAL UNITS TRANSLATION USED IN FRENCH LITERATURE OF THE NINETEENTH CENTURY - Kholova Shahnoza Davronovna (Journal Park Publishing, 2022)
This article lists the terms most commonly used in phraseology. Phraseological units are defined as phrases, one of their main types. There are also examples of phrases used in the novel " Misérables " by the famous French writer Victor Hugo. We had show the alternatives and differences of these phraseological units in French and Uzbek languages.
Keywords: phraseology, phrasema, term, phraseological unit, word, meaning, expression, ways.